Improving evidence for video-assisted thoracoscopic surgery lobectomy - Holbek, Bo Laksáfoss; Jessen Hansen, Henrik; Kehlet, Henrik; Petersen, René Horsleben (AME Medical Journal, 2017)
As thoracic surgeons, we strive to improve treatment with each procedure and aim at performing low-risk operations with an optimal oncologic outcome. Although the number of randomized controlled trials (RCTs) in thoracic surgery has increased, there are still relatively few RCTs published within the field and much of the existing evidence is based on retrospective studies (1).